Superiorly based platysma myocutaneous flap for reconstruction of intra oral defect following fibrotomy in oral submucous fibrosis: Report of a case. Issue 2 (March 2018) - Rajkumar, K.; Chowdhury, S.K. Roy; Saxena, Vivek; Sinha, Ramen
Abstract: Platysma myocutaneous flap is a versatile flap that has been used for head and neck reconstruction since more than three decades. It is a versatile flap based on an axial blood supply used for reconstruction of many intra oral defects like cheek mucosae, floor of the mouth etc. We report here a case of Oral submucous fibrosis Grade III treated with a superiorly based Platysma Myocutaneous flap for reconstruction of the post fibrotomy defect. The patient was followed up for a period of one year with excellent functional and aesthetic outcomes.